Assessment of Fish Biomass and Distribution in a Nuclear Power Plant’s Water Intake Zone Using Acoustic and Trawl Methods - Zuli Wu; Yunpeng Song; Guoqing Zhao; Yongchuang Shi; Yumei Wu; Shengmao Zhang (Animals)
The cooling water intake systems of coastal nuclear power plants are frequently clogged by marine organisms in the water intake area. This study uses hydroacoustic (BioSonics DT-X, 199 kHz) and trawling methods (20 mm codend mesh size) to research fish spatiotemporal dynamics. Species composition, seasonal variations in fish abundance, and target strength were analyzed. Pearson’s correlation analysis revealed a significant negative correlation between water depth and resource density. Significant differences in fish abundance and biomass density were observed among seasons and stations. An analysis of dominant species showed that the IRI (index of relative importance) of Collichthys lucidus was highest in February 2023 (5736.54), while Harpadon nehereus had the highest IRI in November 2023 (2309.17). The distribution and abundance estimates of dominant species from acoustic surveys and biological trawling were highly consistent, demonstrating the applicability and reliability of hydroacoustic methods in fish resource assessments. Through the identification of dominant species as well as the distribution patterns of fish within the water intake area, valuable data support can be provided for the confirmation of those organisms that are prone to clogging the cooling water source. Moreover, it lays a solid foundation for the development of relevant protection work.